Biofunctionalized patterned platform as microarray biochip to supervise delivery and expression of pDNA nanolipoplexes in stem cells via mechanotransduction - Mingkui Shen; Yan Hou; Shihui Xu; Jun Tan; Honggang Zhou; Qi Miao; Wanheng Zhang; Yazhou Chen; Nana Wang; Yongtao Wang (Journal of Nanobiotechnology, 2025)
Abstract Biochips are widely applied to manipulate the geometrical morphology of stem cells in recent years. Patterned antenna-like pseudopodia are also probed to explore the influence of pseudopodia formation on gene delivery and expression on biochips. However, how the antenna-like pseudopodia affect gene transfection is unsettled and the underlying trafficking mechanism of exogenous genes in engineered single cells is not announced. Therefore, the engineered microarray biochips were conceptualized and prepared by the synthesized photointelligent biopolymer to precisely manage geometric topological structures (cell size and antenna-like protrusion) of stem cells on biochips. The cytoskeleton could be regulated in engineered cells and large cells with more antennas assembled well-organized actin filaments to affect cell tension distribution. The stiffness and adhesion force were measured by atomic force microscope to reveal cell nanomechanics on microarray biochips. Cytoskeleton-mediated nanomechanics could be adjusted by actin filaments. Gene transfection efficiency was enhanced with increasing cell nanomechanics, which was also confirmed by the evaluation of cell internalization capacity of nanoparticles and DNA synthesis ability. This work will provide a new strategy to study functional biomaterials, microarray chips and internal mechanism of gene transfection in patterned stem cells on biochips. Graphical abstract